A Contrastive Study on Conceptual Metaphor of Sun in English and Vietnamese 20 th Century Poems. - Trương Thị Mỹ Thuận (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims at conducting a contrastive analysis of conceptual metaphor of “sun” in English and Vietnamese 20th century poems in the light of cognitive linguistics. In order to achieve the aims and objectives proposed, the researcher uses the descriptive and contrastive methods in combination with the qualitative and quantitative approaches. There are 400 samples of conceptual metaphor of “sun” collected from 300 English and Vietnamese poems in total. We have found out 13 conceptual metaphor of “sun” in both of the languages. The study has pointed out the similarities as well as the differences of conceptual metaphor of “sun” in English poems and Vietnamese ones. In addition to giving an in-depth understanding of conceptual metaphor of “sun” in both languages, the research is carried out with the hope of contributing to the variety of conceptual metaphors. Furthermore, the implications of the thesis could be a useful reference for those who are interested in teaching, learning and translating conceptual metaphors in general and those of “sun” in particular.